EFFECT OF HATHA YOGA SADHANA AND SIMPLIFIED KUNDALINI YOGA ON SELECTED PHYSIOLOGICAL VARIABLE AMONG GERIATRIC MEN WITH LOW BACK ACHE - S. Kamalakannan; V. Duraisami (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The purpose of the present study was to find out the effect of hatha yoga sadhana and simplified kundalini yoga on selected physiological variable among geriatric men with low back ache. The study was conducted on 45 Geriatric men with low back ache Totally three groups, namely, control & experimental group I & II, consisting or 15 Geriatric men with low back ache underwent six weeks practice in Hatha yoga sadhana and simplified kundalini yoga whereas the control group did not under go any type of training. The pulse rate was measured before and after the experimentation using the standard equipment ( Citizen) . The data were analyzed by Analysis of Co-variance (ANCOVA) and it was concluded that the Hatha yoga sadhana and simplified kundalini yoga had significant (P < 0.05) effect on the Pulse rate level.